Guide to rational membrane selection for oily wastewater treatment by membrane distillation - Zhang, Xiaocheng (2023)
Membrane wetting and fouling are two major challenges in membrane distillation (MD), especially when the feed has components with low surface tension. A series of membranes with different wettability were developed herein to provide rational guidelines for membrane selection to treat these wastewaters. The membranes with different wettability, and Janus membranes composing of same hydrophilic surface but different substrates (hydrophobicity, superhydrophobicity, superomniphobicity), were made by electrospinning and modifications. It was found that when the feeds had anionic and cationic surfactants, the superhydrophobic and superomniphobic modifications improved their anti-fouling/wetting properties. However, both membranes were rapidly wetted when the feeds had nonionic surfactant Tween-20. The Janus membranes could not delay membrane fouling/wetting when treating the feeds with free surfactants. It even worsened membrane performance as the hydrophilic layer absorbed the surfactants and accelerated membrane fouling/wetting. Regarding the emulsified oily wastewaters, the hydrophilic layer on Janus membranes did show obvious improvement in their anti-fouling/wetting abilities. The underwater hydrophobic layer formed a protective layer and impeded oil contact with the underlying substrate, but the choice of the substrate still needed attention. The superomniphobic substrate showed the most excellent stability as it could reject surfactants even if some managed to pass through.